Educação no campo e trabalho: um estudo das escolas municipais rurais de Uberlândia-MG - Silva, Ana Cecília Oliveira (2011)
The purpose of this paper is to discuss the educational project of the rural schools of Uberlândia/MG and to see how the project meets the specific needs of students in the field as presents in the LDB-9,394/69. The methodology included extensive literature review and research in papers about the subject and field research with application of questionnaires with semi-structured interviews to schoolmaster and school s pedagogical coordination. The fieldwork was conducted in the first half of 2009 in five Rural Municipality School selected according to criteria of location and characteristics of the community surrounding the school. It was noted that the management model, the content, the projects and the training of teachers from rural schools follow the same logic of urban schools, confirming the current neo-liberal thesis that modernization is synonymous of urbanization of society. See the mere adaptation of educational service offered in the city to the countryside, subjecting the peasant population to this template which disregards their culture and is decoupled from their experiences. It was concluded that the education offered in the schools of countryside reproduces the hegemonic values of bourgeois capitalist society even more precarious than in city and this education is contributing very little to a critical social formation of the subject itself and in the transformation of the socio-cultural environment and educational in which he lives.